Mobile Phone Learning and Academic Performance: Examining Gender as Moderating Factor - Pokharel, Ashika; Thapa, Dikshya; Tamang, Anish; Poudel, Apekshya; Gautam, Binshika; Mahat, Dipak (Lembaga Yasin AlSys, 2025)
Background: Mobile learning has emerged as a transformative tool in education, offering flexibility and accessibility for students. However, its role in enhancing academic performance remains underexplored, particularly in the context of gender dynamics. This study investigates the relationship between mobile learning, academic performance, and the moderating influence of gender, providing insights for leveraging mobile technologies in educational settings. Methods: This research employed a quantitative research approach using a cross-sectional survey to collect quantitative data from 156 students across three faculties at Shanker Dev Campus. A structured questionnaire measured mobile learning, academic performance, and gender. Data analysis was performed using SPSS, incorporating inferential statistical tools to analysis. Results: The analysis revealed a significant positive correlation between mobile learning and academic performance. Regression results demonstrated that mobile learning accounts for 40.2% of the variance in academic performance, highlighting its substantial impact. Gender had a small yet significant independent effect on academic performance. However, moderation analysis indicated that gender does not significantly alter the relationship between mobile learning and academic outcomes. Conclusion: The findings underscore the effectiveness of mobile learning in improving academic performance, with gender differences playing a minimal role in this relationship. Integrating mobile learning into educational strategies can benefit students across diverse demographics. Novelty: This study uniquely explores gender's moderating role in mobile learning's impact on academic performance, offering new perspectives on equity and inclusivity in technology-driven education.